Aroura – the soil and soil security think tank - Styc, Quentin; Evangelista, Sandra J.; Watt, David; Wensley, Penelope; Heuser, Irene; Pachón Maldonado, Julio C.; Feeth, Julia; Francos, Nicolas; Hunakunti, Anilkumar; Jayasekara, Thilini; Borrelli, Pasquale; Field, Damien; et al. (Frontiers in Environmental Science, 2025)
Soil, a fundamental resource for life on Earth, has faced increasing degradation, particularly over the past century, with its ability to support ecosystems and human wellbeing rapidly deteriorating. Despite its critical role, soil remains largely neglected in global policy agendas. In response to this urgent issue, Aroura, The Soil and Soil Security Think Tank was established to raise soil security to the forefront of global priorities. The Think Tank unites a wide range of experts from fields such as politics, law, economics, and soil science, working together to address the global need for sustainable soil management. Soil is deeply interconnected with all of Earth’s life-supporting systems, playing a vital role in solving major global challenges, including biodiversity preservation, climate change mitigation, food and water security, and human wellbeing. Effective soil management can be both a challenge and a solution, depending on the approach taken. To guide effective soil management, Aroura promotes the Soil Security Assessment Framework, which includes not only the biophysical aspects of soil but also its socio-economic, cultural, and political dimensions. The Think Tank was launched in 2024, following the Inaugural Global Soil Security Summit in Sydney, Australia, attended by invited experts from six continents. The Summit participants created and signed the Soil Security Declaration and established a set of Soil Policy Principles to help shape global policies on soil. Aroura’s objectives are to: i. raise awareness of the importance of soil and the need to take urgent action to assure soil security, ii. foster cross-disciplinary collaboration and iii. advocate for evidence-based policies and laws to ensure sustainable soil management. By securing soil, Aroura aims to safeguard life itself, ensuring a resilient, thriving planet for both current and future generations.